REMOVAL OF METHYLENE BLUE BY USING GREWIA ORBICULATA ROTTL . ( ZINGROOL TREE) AS BIOSORBENT - P.BANGARAIAH; P.ASHOK KUMAR (International Journal of Pharma and Bio Sciences, 2013)
This investigation handles the adsorption of methylene blue dye from aqueous solution using “Grewia orbiculata Rottl.” Leaves. Effects of different parameters such as agitation time, adsorbent size, adsorbent dosage, initial concentration of methylene blue in aqueous solution, volume, pH of aqueous solution on removal of methylene blue are determined. From these investigations, one gram of “Grewia orbiculata ” Leaf powder of 82.5mm size is found to remove 90% of 20 mg/l methylene blue from 30ml of aqueous solution in 30min. These results indicate that adsorption of methylene blue is increased with an increase in adsorbent dosage and decrease in adsorbent size. A significant increase in percentage removal of methylene blue is observed as pH value increased from 4 to 7.28 and percentage removal is marginally increased from 1 to 4. The percentage removal decreased as pH value increased beyond 7.28. Freundlich and Langmuir isotherm models describe the adsorption data very well indicating favorable adsorption of methylene blue adsorbent. Freundlich isotherm is relatively more suitable than Langmuir isotherm. Hence based on results obtained it is found that Grewia orbiculata Leaf powder is effective in methylene blue removal and can be appreciably considered as most versatile, economical and feasible adsorbent for removal of methylene blue from aqueous solutions.